The CPNE Family and Their Role in Cancers - Tang, Haicheng; Pang, Pei; Qin, Zhu; Zhao, Zhangyan; Wu, Qingguo; Song, Shu; Li, Feng (Frontiers in Genetics, 2021)
Lung cancer accounts for the leading cause of cancer-related deaths worldwide. 85% of lung cancer is non-small cell lung cancer (NSCLC). Despite significant advances in cancer research and treatment, and some progress has been made, the overall prognosis of patients with non-small cell lung cancer remains poor. The reason is that most lung cancer patients are in the middle and late stages of treatment. Therefore, early diagnosis and early treatment of lung cancer are directly related to the prognosis of patients. Although various imaging, biopsy and histopathological analysis are widely used, there is a lack of effective biomarkers to detect early lung cancer, especially non-small cell lung cancer. Therefore, the search for novel biomarkers as therapeutic targets is critical for the treatment of non-small cell lung cancer. CPNEs (copines) are a family of membrane-bound proteins that are highly conserved, soluble, ubiquitous, calcium-dependent, and present in a variety of eukaryotes. Recent studies suggest that they may mediate a variety of signaling pathways involved in tumor proliferation and metastasis. Among the CPNE gene family, CPNE1 (copine1) is a novel participant in the regulation of proliferation and metastasis of non-small cell lung cancer. This review highlights CPNE1 as a prognostic marker and a potential therapeutic target for the effective treatment of patients with non-small cell lung cancer.